The Use of Pusako Tinggi to Support Children's Education In Nagari Salingka Muaro, Sungai Aur District, West Pasaman Regency - Rahmatul Fajriah; Yuhelna; Isnaini (UNIB Press, 2025)
This study was motivated by the use of pusako tinggi to finance children's education in Nagari Salingka Muaro, West Pasaman Regency. Pusako tinggi is an inherited asset from the female side that cannot be sold without the community's consent, because it serves not only as an economic asset but also as a symbol of the family's social continuity. However, in modern society, pusako tinggi is often used or even sold to meet urgent needs, including education. This study uses a qualitative, descriptive approach. The theory used is Herbert Spencer's theory of social change. Informants were purposively selected, and data were collected through in-depth interviews, observations, and document analysis. The unit of analysis was clans that sold high pusako for their children's education. Data analysis employed Miles and Huberman's interactive model. The results showed that the use of high-purpose savings accounts supported family life, particularly for children's education expenses. This reflects that Minangkabau customs prioritise education, as children are seen as inheritors of family dignity and continuity. However, the practice of utilising high-pusako for education often creates internal dilemmas and conflicts, given its communal rather than private ownership.